Public Employee Accountability in Official Family Planning and Population Control (DPPKB) Bekasi Regency - Kristian Widya Wicaksono; Kania Anggraeny Ramadhan (Universitas Sultan Ageng Tirtayasa, 2022)
Accountability of the State Civil Apparatus (ASN) in the Official Family Planning and Population Control (DPPKB) Bekasi Regency experienced a problem because they could not look closer to each other in the work deployment. Furthermore, as part of public employee accountability, the people of Bekasi Regency lack a channel to monitor the performance of the ASN in the DPPKB of Bekasi Regency. This research aims to describe the accountability of ASN in DPPKB Bekasi Regency. This study utilized Han and Perry's Public Employee Accountability theory. This theory has five dimensions: attributability, observability, evaluability, answerability, and consequentiality. The quantitative approach is used in this study. Surveying is a type of research. Data is collected by distributing questionnaires to all DPPKB Bekasi Regency employees. Consequently, the sampling technique used in this study was a saturated sample, in which the entire population of 40 ASN in DPPKB was sampled. Furthermore, the data were analyzed using a univariable descriptive statistical analysis method that measures the frequency distribution, the central tendency, namely the median, and the distribution of the variability studied, namely the interval index. According to the findings of this study, most ASN within the DPPKB Bekasi Regency have demonstrated accountability as public employees in executing their duties since they can be asked to explain actions taken or not taken against stakeholders with confidence in the outcomes based on the evaluation results.